Off-label use of antimicrobials among hospitalized children: a retrospective study of 3,406 patients - Tang, Lin; Zhao, Kai; Hou, Ning (Frontiers in Microbiology, 2023)
Off-label drug use (off-label) is a global problem for which many countries and regions have issued legal provisions or expert consensuses. However, the applicability of these consensuses in pediatric patients has not been evaluated. Off-label use is sometimes a necessity, especially since antibacterial drugs have become one of the most widely used drugs in pediatric settings, and causing antimicrobial resistance has increasingly become an inescapable issue. It also poses additional risks, for example, adverse drug reactions. Our study retrospectively analyzed the antimicrobial prescriptions of pediatric inpatients in a large Chinese hospital in the first half of 2021. It was found that off-label antibiotics were present in many children (n = 1,665, 48.9%) and were most common in newborns (n = 328, 82.8%). Among the commonly used antibiotics in pediatric patients, cephalosporins (n = 2,778, 40.7%) accounted for a relatively low proportion of off-label use (n = 360, 15.7%), while macrolides (n = 628, 27.4%) and penicillins (n = 610, 26.6%) accounted for a higher proportion. The off-label type mainly referred to the appropriate population (46.5%) and dosage (dose, 10.0%; frequency of administration, 48.3%). Off-label use was due to imperfect labels and improper medications or medication errors. The most current consensus has not been applied to pediatric patients. More clinical trials are needed to update the consensus, and drug labels must be continuously improved. Doctors’ prescription practices also need to be standardized.